Accreted Terranes and Porphyry Copper Deposits in the Central Andes (The Australasian Institute of Mining and Metallurgy, 1995)
The Central Andes in Peru, Chile, Bolivia, and Argentina , contain two contiguous terranes which were accreted to Gondwanaland between the end of the Devonian and the end of the Triassic. These terranes, Arequipa in the north, and Chilenia in the south, differ from each other in the timing and style of their metallogenic development. However, they contain over 90% of the Central Andean porphyry copper resource. The copper porphyries in the Arequipa terrane are Paleocene to lower Oligocene in age, whereas the Chilenia deposits are mid-upper Cretaceous and mid-upper Miocene. Porphyry copper deposits occur outside these terranes, but are all Miocene in age. Miocene porphyry-style mineralisation also exists in the Arequipa terrane, but is copper-deficient and gold-rich. The accreted terranes may have favoured porphyry and other styles of copper mineralisation because they possessed relatively thin continental crust compared to adjacent parts of the Andes. Crustal thickening which commenced at about 30 Ma in the Arequipa terrane coincided with a major change to polymetallic, precious metal mineralisation which commonly displays high sulfidation characteristics.